Simple synthesis of Fe3O4@Fe3S4 Nanocomposites coated with polyindole-polythiophene for high-performance supercapacitor - Asgharinezhad, AliAkbar; Niknam, Ehsan; Larimi, Afsanehsadat (Journal of Composites and Compounds, 2023)
To prevent a major energy crisis in the near future, it is necessary to assemble efficient electrochemical energy storage devices such as supercapacitors. Herein, a Fe3O4@Fe3S4 nanocomposites coated with polyindole-polythiophene on nickel foam (NF) has been prepared by following a low facile, multistep method. In terms of structural and electrochemical performance, the nanocomposites have been investigated. The electrochemical properties of as fabricated Fe3O4@Fe3S4@PIn-PTh are studied in 2M KOH. A specific capacitance of 100.83 F g-1 at a current density of 2 A g-1. The results of the synthesized sample in comparison with Fe3O4 show that using sulfide metal and polymer component improve the electrochemical performance. These characteristics of Fe3O4@Fe3S4@PIn-PTh as the active material illustrate a sutiable performance as a cathode material for electrochemical energy storage.